2021
DOI: 10.9744/jmk.23.1.40-51
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate Students’ Perceptions and Attitudes Towards a Career in Tourism Industry: The Case of Indonesia

Abstract: As a world-class tourism destination, Indonesia is facing challenges in providing competent tourism human capital. Currently, the majority of tourism labor in Indonesia are low levels of education and only a few of them are graduated from higher education. Empirically, numerous studies suggest that many graduates from various tourism schools in several countries preferred to not opt for the tourism careers. This study aims to discover and analyze the perceptions and attitudes of final year students majoring in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Not only does it help institutions and colleges attract students, but it also helps instructors build practical courses by understanding how students see things. In accord with this, Rosyidi (2021) found that 90.5% of 422 respondents desired to work in the tourism industry prior to COVID-19. When the circumstances changed to "after COVID-19," the figure dropped 81.5 percent.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Not only does it help institutions and colleges attract students, but it also helps instructors build practical courses by understanding how students see things. In accord with this, Rosyidi (2021) found that 90.5% of 422 respondents desired to work in the tourism industry prior to COVID-19. When the circumstances changed to "after COVID-19," the figure dropped 81.5 percent.…”
Section: Introductionmentioning
confidence: 75%
“…Student interns' engagement in the field and direct contact with tourists is another feature of work in the tourism business. Students believe that internship programs are essential for improving skills and gaining job experience, although they must be willing to work without pay, according to the study by Rosyidi (2021). As a result, such programs are critical for students, particularly during the present pandemic, to assuage their anxieties about their prospects in the tourism industry.…”
Section: Job Opportunities In the New Normalmentioning
confidence: 99%
See 1 more Smart Citation
“…Students are more likely to pursue careers in tourism if they perceive it as offering good job opportunities, growth potential, and attractive salaries. Positive perceptions of the tourism industry, including its contribution to economic development, cultural exchange, and environmental sustainability, can attract students to the field [31]. This refined presentation of the theoretical framework provides a comprehensive and scholarly basis for examining the impact of Industry 4.0 on the Indian tourism workforce.…”
Section: Assessing Faculty and Student Perceptionsmentioning
confidence: 95%
“…Students' level of interest comes from their experience, and it would be determined whether students are keen to work in the hospitality industry after entering an internship (Rosyidi, 2021). Thus, to fit the demand for more leisure and commitment toward a career, there is the possibility of redefining the work practices and lifestyle in the hospitality industry (Zahari, 2004).…”
Section: Level Of Interest and Commitmentmentioning
confidence: 99%